(3GdJQLjM dMOjK UdGI GdJSHjMs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3fLe GdOjf YeQ Hf eMeO Hf agPG GdgGTei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi SHM faSg JYXjekG hHYO aEf Gddg SHMGfg hJYGdi CaGV Ydi Ndbg EMSGfg s
(3BNQgG (B:s
(3eG JhGdi GdUHGM eY LfM djd hJhGQi eZjH ai VQjM BNQ GdJQLjM dMOjK UdGI GdJSHjM s
(3HgG fXGe G dJYbjHIs
(3cJHJ HNW eged GdfbW fbdJ Yf fSNI HNW GdeDda hYdi MGTjI fSNJfG gPg SeGY heYGQVI HNW GdeDda HBNQgG SeGY SfI (B837 (3Ydi GdeDda ef YOI YdeGA hGdfGSN faSg hTgO GdeDda Ydi gPG GdSeGY hELGRI HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
Keywords: (3GdMOjK h GdeUWdMs